1997
DOI: 10.1177/08959374970110042501
|View full text |Cite
|
Sign up to set email alerts
|

Zeta Potentials of Human Enamel and Hydroxyapatite as Measured by the Coulter® DELSA 440

Abstract: The zeta potential of human enamel is of physiological importance for interactions between enamel surfaces and the surrounding aqueous medium of saliva. The zeta potentials of both enamel and hydroxyapatite (HA) have been examined previously by various techniques. In this study, we examined the zeta potential of human enamel and HA using the Coulter DELSA 440, which, by a laser, makes independent Doppler shift measurements of moving particles in an electric field at 4 different angles, providing advantages ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 16 publications
2
52
0
5
Order By: Relevance
“…In a study by Young 15) , the zeta potentials of human enamel and hydroxyapatite particles became less negative after adsorption of parotid or whole saliva. In a study by Shimomura 11) , the zeta potential of the surfaces of hydroxyapatite plates became less negative after protein adsorption.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Young 15) , the zeta potentials of human enamel and hydroxyapatite particles became less negative after adsorption of parotid or whole saliva. In a study by Shimomura 11) , the zeta potential of the surfaces of hydroxyapatite plates became less negative after protein adsorption.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that chitosan is capable of interfering with S. mutans adhesion and primary biofilm formation [21][22][23] . Chitosan is also known as a bioadhesive polymer 24) that may interact with the negatively charged hydroxyapatite surface of enamel as well as with the negative cell wall of biofilm bacteria 25) . These kinds of interactions would be responsible of the higher copper retention on the biofilm/enamel surface (EDX mapping) and the improved anti-biofilm action exhibited by CuChNP.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that chitosan can form a layer-by-layer build-up on dental enamel, providing better protection against erosive attacks . This layer is formed because chitosan has a strong positive zeta potential, and it can readily adsorb to surfaces with a strong negative zeta potential [Claesson and Ninham, 1992], such as enamel [Young et al, 1997]. Chitosan was also shown to adsorb onto salivary pellicle proteins [Sano et al, 2001;van der Mei et al, 2007].…”
Section: Products Containing Other Proteins or Polymersmentioning
confidence: 99%